Analysis of Tissue Repair of a New Cement Based on Calcium and Strontium Aluminates: A Triple-Blinded, Randomized, Controlled Trial in an Animal Model - Penha, Elizandra Silva da; Filho, Nonato Amorim de Farias; Medeiros, Luanna Abílio Diniz Melquíades de; Rosendo, Rosana Araújo; Silva, Marco Antônio Dias da; Barbosa, Willams Teles; García-Carrodeguas, Raúl; Rodríguez, Miguel Angel; Münchow, Eliseu Aldrighi; Lacerda-Santos, Rogério; Fook, Marcus Vinícius Lia (European Journal of Dentistry, 2024)
Objective The focus of this triple-blind randomized study was to evaluate the biocompatibility of a new root canal filling sealer (RCFS) based on tristrontium aluminate and dodecacalcium hepta-aluminate in living tissue.Material and Methods Forty-five Wistar rats (Rattus norvegicus) were divided into three groups: control (polyethylene), sealer (Bio-C Sealer, Londrina, PR, Brazil), and experimental (tristrontium aluminate and dodecacalcium hepta-aluminate). The tissues were analyzed under an optical microscope to assess different cellular events at different time intervals (7, 15, and 30 days).Statistical Analysis Data were analyzed using the Kruskal–Wallis and Dunn (p < 0.05) tests.Results In the initial period, a moderate inflammatory infiltrate was observed, similar between the endodontic cements groups (p = 0.725). The intensity of the infiltrate decreased with time, with no significant difference among the groups (p > 0.05). The number of young fibroblasts was elevated in all groups evaluated at 7 days. The experimental group showed the highest number of cells at all time intervals, but the difference with the sealer group at 7 (p = 0.001) and 15 days (p = 0.002) and the control group at 30 days was not significant (p = 0.001). Regarding tissue repair events, the amount of collagen fibers increased over the experimental intervals, with no significant difference between the sealer and control groups (p > 0.05).Conclusion The experimental RCFS based on calcium and strontium aluminates proved to be biocompatible for use in close contact with periapical tissue, inducing a low inflammatory reaction and favoring rapid tissue repair.
Keywords: microscope; biocompatibility; histology; root canal filling sealer